Long-term evaluation of the prognosis of super hydrophilic surface treated CA implants: a retrospective clinical study - Min-Joong Kim; Il-hyung Kim; Na-Hee Chang; Young-Kyun Kim (BMC, 2022)
Abstract Background This study was performed to evaluate the long-term clinical efficacy of the CA implants (Osstem Implant, Busan, Korea), calcium-modified surfaced treated implants on acid-etched surfaces sandblasted with alumina. Methods From January 2013 to December 2015, 258 implants of 120 patients placed between 2013 and 2015 were retrospectively studied. Using medical records and periapical radiographs, sex, age, location, fixture width and length of placed implants, presence or absence of bone graft, types of bone substitutes and membrane used for bone grafting, primary and secondary stability, initial and delayed complications, and marginal bone loss were investigated. The success rate and survival rate of the implants in each group were analyzed retrospectively based on the criteria suggested by Albrektsson et al. Results Between 2013 and 2015, with a follow-up longer than 5 years, 258 implants with an average diameter of 4.63 mm (3.5-5.5 mm) and an average length of 9.94 mm (7.0-13.0 mm) were placed in a total of 120 patients (61 males and 59 females) with a mean age of 63.7 years for an average of 62 months of observation period. The survival rate was 97.3%, the success rate was 94.2%, and the average final marginal bone loss was 0.074 mm. Conclusion The CA implants manufactured with the improved surface treatment method exhibited a survival rate of 97.3% and a success rate of 94.2% over an average observation period of 62 months. The implants were not affected by most factors and had very high survival and success rates over a long period of observation. In particular, the stability of the implant was excellent, with no cases of failed implants in delayed placement after bone grafting and a healing period.